THE IMPACT OF POSITIVE MOTIVATION AND NEGATIVE MOTIVATION ON EMPLOYEE WORK PERFORMANCE (Case Study at PT. Actual Kencana Appraisal Surabaya Branch) - Fitria Agus Rina; Mahjudin Mahjudin (PT. Mawadaku Sukses Solusindo, 2024)
The purpose of this thesis research is to determine the extent to which the influence of positive motivation and negative motivation on employee work performance at PT. Actual Kencana Appraisal Surabaya Branch. The problem in this study is whether there is an influence between positive motivation variables and negative motivation variables that have a simultaneous and partial effect on employee work performance at PT. Actual Kencana Appraisal Surabaya Branch. This research is a quantitative study, which uses multiple linear regression analysis techniques. For the sampling method using the saturated sample method, which means that the total number of the population is used as a sample, which is 40 respondents. The data used are primary data sources, namely through the distribution of questionnaires and secondary data sources, namely through archive data/company documents. While to facilitate data processing using SPSS assistance. The results of the SPSS analysis show that there is a strong and positive relationship between motivation and employee work performance, as evidenced by the determinant coefficient (R2) which shows a value of 0.702, this means that the contribution affects the work performance variable by 70.2%. Likewise, the negative motivation variable (X2) which has the most dominant influence on the work performance variable (Y), this shows that the influence between motivation and employee work performance has a strong and positive influence, where the increase in employee motivation levels will be followed by an increase in their work performance. This is evidenced by the large standard b of 0.655 and the calculated t of 6.099 which is greater than the other calculated t.